170 Meta-analysis to Determine the Standardized Ileal Digestible Lysine Requirements of Growing-finishing Pigs from 11- to 150-kg - Orlando, Uislei A (J Anim Sci, 2021)
A meta-analysis was conducted to determine the standardized ileal digestible (SID) lysine (Lys) recommendations for 11–150 kg PIC pigs housed under commercial conditions. Data from 29 trials dating from 2013 to 2020 utilizing 48,338 pigs were recorded in a database. Number of pens/treatment and pigs/trial ranged from 9 to 16 and 12 to 25, respectively. Sire lines were PIC 337 in 25 trials, PIC 327 in 3 trials, and PIC TR4 and 327 in 1 trial. Dam lines were PIC Camborough in 18 trials and PIC Camborough 29 in 9 trials. The SID Lys to calorie ratio curves were built for both metabolizable energy (ME) and net energy (NE) systems using the feed ingredient composition in NRC (2012) for energy levels. The response variables average daily gain (ADG) and feed efficiency (G:F) were analyzed using generalized linear and non-linear mixed models with heterogeneous variance (Gonçalves et al., 2016). Each treatment mean within a trial (n = 288) was considered the experimental unit and each trial was used as a random effect. The models were developed for mixed gender pigs and the PIC 337 growth curves were used to estimate the recommendations for barrows and gilts. There was no evidence for an interaction between sire lines or dam lines and treatment (P > 0.10). The SID Lys to calorie recommendations are based on the average for ADG and G:F (Table 1). At these levels, approximately 100% of maximum ADG and 99.4% of maximum G:F are achieved. The NE to ME ratio that results in a similar SID Lys recommendation as a percentage of the diet ranged from approximately 0.72 to 0.74. The updated biological requirements for PIC pigs remained similar compared to previous PIC recommendations (Gonçalves et al., 2017). However, the requirement estimates have been adjusted for late nursery and late finishing phases. [Image: see text]